Generation of homogeneous glow discharge using a combination of fine wire mesh perforated aluminium alectrode - Sahari, Norain (2013)
Nowadays, a gas discharge plasma applications has rapidly extended due to the greatest chemical freedom offered by the non-equilibrium aspects of the plasma. Among the applications of gas discharge plasma are surface treatment, air pollution control, lasers, lighting, plasma displays, ozone generation and biomedical applications. The most commonly used in plasma industry is the glow discharge plasma. It is known to be generated under high vacuum condition. At low pressure glow discharge plasma, the producing of surfaces and thin films are more effectives and good quality. But, this technique gives disadvantages due to the large cost to maintain at low pressure condition. However, there were many researches that have been done to produce glow discharge at atmospheric pressure. This glow discharge can be stabilize at atmospheric pressure if three simple requirements are fulfilled: (i) use of source frequency of over 1 kHz, (ii) insertion of a dielectric plates between the two metal electrodes, (iii) use of helium dilution gas. Used of helium gas is impractical due to its high cost. In order to generate glow discharge at atmospheric pressure in any gases, it was found that fine wire mesh and perforated aluminium can maintain a stable glow discharges. This thesis focus on the production of homogeneous glow discharge by using a combination of fine wire mesh and perforated aluminium as electrodes. A study was also made to determine the effect of a frequency and gap spacing on the stability of glow discharge